Pengaruh Metode Demonstrasi Terhadap Motivasi Belajar Siswa pada Mata Pelajaran Matematika di Kelas V SDN 105305 Mardinding Julu Tahun Ajaran 2023/2024 - Br. Ginting, Cica; Ramadhan, Nuri; Ramadhani, Mastari (Multiverse: Open Multidisciplinary Journal, 2024)
The influence of the demonstration method on students' learning motivation in fifth grade elementary school mathematics subjects. This research is motivated by the researcher's hypothesis which suspects the influence of the demonstration method on student learning motivation. The aim of this research is to find out how much influence the demonstration method has on student learning motivation. This research was carried out at SDN 105305 Mardinding Julu. The method used is a survey method using a questionnaire. The sample used in this research was 35 students. The instrument given was a questionnaire with a demonstration method statement of 14 statements. Learning motivation instrument 21 statements. Data analysis uses simple regression and coefficient of determination. The results of the hypothesis test in determining the regression equation, obtained a calculated t value = 4.121 with a significance value of 0.001 <0.05, so H0 was rejected and Ha was accepted. This means that the demonstration method at SDN 105305 Mardinding Julu has an influence on the atmosphere of learning motivation. The demonstration method in class V at SDN 105305 Mardinding Julu has an influence contribution value of 47.2%, while the remaining 53.8% is influenced by other variables outside the research or also known as non-determination coefficients such as telling stories, prayers or words. , singing in groups, and group activities in accordance with existing teaching techniques at SDN 105305 Mardinding Julu.